Effects of sodium tungstate on oxidative stress enzymes in rats. (September 2013) - Sachdeva, Sherry; Kushwaha, Pramod; Flora, S. J. S.
Abstract Tungsten, due to its distinguished physical properties, has wide industrial and military applications. Environmental exposure to tungsten, which mainly occurs through various sources like food, water, soil, etc., is of growing concern as various toxic effects have recently been reported. In this study, we investigated the effects of oral and intraperitoneal (i.p.) administration of sodium tungstate on various biochemical variables indicative of oxidative stress in erythrocytes and soft tissue damage in rats. Male rats were administered to 119 mg, 238 mg/kg of sodium tungstate orally or 20 mg and 41 mg/kg through i.p. route, for 14 consecutive days. The results demonstrated a significant increase in Reactive Oxygen Species (ROS) and an increase in catalase and glutathione peroxidase antioxidant enzymes activities in erythrocytes. Erythrocyte glutathione-S-transferase (GST) activity showed significant inhibition, while tissue ROS and thiobarbituric acid reactive substance levels increased accompanied by a decreased reduced glutathione, oxidized glutathione (GSH:GSSG) ratio. These changes were supported by an increase in plasma transaminases activities, creatinine, and urea levels, suggesting hepatic and renal injury. These biochemical alterations were prominent in rats intraperitoneally administrated with sodium tungstate than oral administration, suggesting more pronounced toxicity. The study also suggests oxidative stress as one of the major mechanism involved in the toxic manifestations of sodium tungstate.